HUBUNGAN PERSEBARAN EPISENTER GEMPA DANGKAL DAN KELURUSAN BERDASARKAN DIGITAL ELEVATION MODEL DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - , DENDI BORNEO PUTRA, Ir. Djoko Wintolo., DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study has the purpose to evaluate the earthquakes data that occurred in the study area over a period of 14 years with a research focus on earthquake studies, determination of the surface structure, and correlation between two of them. The research area include the area of Yogyakarta region. Yogyakarta is an aera which is frequently hit by the earthquakes, because of the location that fall under the ring of fire. The earthquakes that are studied generally has shallow depth, between 10km to 15 km, with a magnitude of 3-7 magnitude SR. by using earthquake data downloaded from the USGS and obtained from BMKG Yogyakarta, the epicenter of the earthquake can be projected into the map for the research. The study was conducted by projecting epicenter earthquake point on a map, assisted by regional geological map, straight pattern from DEM. Then it will conclude the connection between the point of the epicenter of the earthquake occurred, and the location of the surface structure. From the results of research studies Yogyakarta earthquake, found that 2006 is the year in which has the highest frequency of occurrence of earthquakes with the largest magnitude up to 6, 4 magnitude ritcher scale. While on the surface structure of the study, showed that the distance between the epicenter of the earthquake to the structure of the surface has a little variation with a little bit diversity. As the result of a standard deviation between 1-4 km, it can be conclude that the epicenter of an earthquake in study area has close proximity to the surface structure.